2009
DOI: 10.1177/1524838008327260
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence Against Women and Children in Chinese Societies

Abstract: This article provides a comprehensive overview of the reported patterns of sexual violence against women and children in China. It reviews the prevalence of and risk factors for various types of sexual violence and discusses community knowledge and perceptions of these violent acts. It also critically examines three major problems of sexual violence research in China. First, the diversity of findings and study methods reported by surveys and criminal reports reflects the problems in obtaining accurate figures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 61 publications
1
24
0
2
Order By: Relevance
“…To identify additional relevant studies, we contacted 18 researchers and organizations involved in child protection in China and checked the reference lists of key narrative reviews on child maltreatment in or around China. 6 , 13 , 14 , 16 , 17…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify additional relevant studies, we contacted 18 researchers and organizations involved in child protection in China and checked the reference lists of key narrative reviews on child maltreatment in or around China. 6 , 13 , 14 , 16 , 17…”
Section: Methodsmentioning
confidence: 99%
“… 6 There have been no national assessments of child maltreatment and only a few comprehensive provincial studies. However, the results of early descriptive surveys of child sexual 7 – 10 and physical abuse 11 and some more recent relevant data 12 , 13 have been included in global and regional reviews. 2 , 3 , 14 , 15 There has also been one systematic review that focused solely on the prevalence of child sexual abuse in China.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, earlier research among Chinese societies indicated that parents' reports are unlikely to reveal the true prevalence of child sexual abuse (Chan, 2005(Chan, , 2008. Lin et al's (2016) focus, hence, was on physical abuse, emotional abuse, and emotional neglect.…”
Section: Charak and Kootmentioning
confidence: 99%
“…Asian societies, including Chinese populations, are believed to have cultures and traditions that can be very different to those of Western populations. These specific cultural backgrounds, such as patriarchal authority and the principle of filial piety and unquestioning obedience for children in China, may lead to different patterns of prevalence or reporting of child maltreatment (Chan 2009b). Indeed, past findings have often revealed a higher tolerance for parental physical aggression as disciplinary practices among Chinese populations (Hong and Hong 1991; Wong et al 2009).…”
Section: Correlates Of Child Maltreatment and Its Reportingmentioning
confidence: 99%